Improvement of electric discharge machining (EDM) performance of Ti-6Al-4V alloy with added graphite powder to dielectric - Unses, Emre (Strojniški vestnik, 2015)
Ti-6Al-4V is a well-known Ti alloy widely used in the aerospace industry and belongs to the group of difficult-to-machine materials. It is less suitable for both conventional chip removal (machining) techniques and electric discharge machining (EDM). The very low material removal rate (MRR) of the Ti alloys during the EDM process causes prohibitively long machining durations. The goal of this study was to improve the EDM performance of the Ti-6Al-4V alloy by the addition of graphite powder into the kerosene dielectric liquid. The EDM performance was quantified by MRR, tool electrode wear rate (EWR), relative wear (RW), surface roughness and texture properties. The experiments conducted have shown that the use of graphite powder mixed with the kerosene dielectric (GPMKD) during machining considerably increases the MRR, improves the R a and R z(DIN) surface roughness and decreases the RW. 3D topographic views of the machined workpiece surfaces attained with GPMKD revealed uniformly distributed surface valleys and peaks over the surface and peaks with short and round tops since the discharge energy of a spark is distributed over a large area at the machining gap. The experimental results strongly indicate the adaptability of the proposed technique to EDM die sinking and EDM drilling applications of the Ti-6Al-4V alloy in the aerospace industry. The ED machining performance of Ti-6Al-4V alloy using GPMKD is also compared to that of AISI 1040 steel, which is commonly used in EDM applications.
Keywords: 3D-topografija površine; elektroerozijska obdelava; grafitni prah; hrapavost; obraba orodne elektrode; odstranjevanje materiala; Ti-6Al-4V